Smartphone Use in Everyday Life and Travel - Wang, Dan; Xiang, Zheng; Fesenmaier, Daniel R. (Journal of travel research, 2016)
The smartphone penetrates many facets of everyday life, including travel. As such, this article argues that since travel can be considered a special stage of technology use, understanding how the smartphone shapes the tourist experience cannot be separated from the way it is used in one’s everyday life. On the basis of a study of American travelers, this study uses adaptive structuration theory as a lens to identify a number of spillover effects from smartphone use in everyday life into travel. The results of this study offer several important implications for both research and practice as well as future directions for the study of mobile technology in tourism.